Firm characteristics and dividend policy in India. Issue 3 (3rd July 2017) - Das, Santanu
Abstract: This article studies the determinants and evolution of dividends of BSE 500 companies in India over a period from 2001 to 2015. It finds that although these firms have been paying dividends, they are not consistent. In India, dividends are more determined by the availability of profits and liquidity. The speed of adjustment coefficients which is estimated using the Lintner model, are found to be high and statistically significant over the sample period. Results from the study reveal that although leverage is an important determinant of dividend, size is not. In this study, two important research questions arises regarding studying quality of earnings and the reluctance to adopt and predictable dividend policy.